Penerapan Penerapan Media Pembelajaran Power Point Interaktif dalam Menanamkan Sikap Cinta Tanah Air Siswa Kelas V di SD Negeri 2 Meurandeh - Ainun Fadillah; Lhutfia Wahyu Safutri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to determine the effectiveness of implementing Interactive PowerPoint learning media in instilling love for the homeland attitudes of fifth grade students at SD Negeri 2 Meurandeh and to determine students' responses to the use of this media. This research is a quantitative descriptive study with a survey approach conducted at SD Negeri 2 Meurandeh with 22 fifth grade students as research subjects. The research instrument used was a psychological scale questionnaire with a 5-point Likert scale consisting of 25 statements with five dimensions: active student involvement, material understanding, teamwork and group discussion ability, application of love for homeland values, and motivation and learning enthusiasm. The results showed that the implementation of Interactive PowerPoint learning media in instilling love for the homeland attitudes of fifth grade students at SD Negeri 2 Meurandeh was in the